Tourism and Economic Growth: Evidence from ASEAN countries - Devi Indriani (Journal of Indonesian Applied Economics, 2022)
Tourism has become an important sector in the economy over recent decades, but the impact of tourism on economic growth is still debated. The purpose of this paper is to investigates the long-run relationship between tourism and economic growth in ASEAN countries as well as the causal linkages between them. This study uses panel Autoregressive Distributed Lag (panel ARDL) and data from the World Tourism Organization and the World Development Indicator. The results suggest that tourism has significant and positive impact on economic growth in the long run. Furthermore, the results also indicate that there is bidirectional causality between inbound tourism and economic growth.